DETERMINING THE RELATIVE IMPORTANCE OF INDICATORS OF SUBURBAN PUBLIC TRANSPORT COMFORT BY THE METHOD OF GEOMETRIC MEAN FUZZY-AHP (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Nowadays to commute by train and bus in a number of countries is preferred by population for certain distances such as suburban trips. The comfort level of passengers while travelling by public suburban transport is a combination of physical and psychological factors. In order to analyze how comfort affects the choice of transport on a global scale, a number of studies have been carried out. The indicators affecting passenger comfort include the personal space, vehicle environment, level of service, etc. Commuters with different professions and travelling purposes have different notions of comfort. Comfort influences on the choice of transport mode and because of that the main objective is to determine the criteria, which passengers apply to evaluate its level. Multi-criteria decision making is the field that deals with evaluation of indicators or situations according to multiple conflicting criteria. The methods taking into account the presence of subjective elements in passengers’ preferences for decision-making have been analyzed considering Analytical Hierarchy Process (AHP) and fuzzy-AHP, which is a structured technique for organizing and analyzing complex solutions based on mathematics and psychology. Using the chosen method, multi-criteria decision has been made to determine the relative importance of indicators by geometric mean fuzzy-AHP. The opinions of practitioners, researchers, managers are considered analogously to the relative importance of indicators. A survey has been developed and conducted with commuters to find out the indicators affecting assessment of comfort and quality of public transport. The study made by a group of experts to evaluate the indicators of comfort has applied the derived geometric mean fuzzy-AHP to determine the relative importance of measurement criteria. The results of study would help to increase the comfort offered and attract more passengers to railway suburban transport taking into account the level of indicators and possibilities of their improvement.